Hubungan Antara Identitas Dengan Reputasi Sekolah SMA Negeri 10 Samarinda Kalimantan Timur - Fitria Sari Hasanusi (Peneliti.net, 2019)
The school is the second place of education for children. Schools can become educational identities that have positive and negative meanings. Schools that have strong identities tend to have good perceptions among the community. For this reason, a good reputation is needed to achieve education that has succeeded in bringing students to be human beings, devoted and accomplished. This research is motivated by the problem of School Administration and School Reputation The purpose of this paper is to answer how the identity and reputation of the school in Samarinda 10 SMA, Kalimantas Timur. The approach method used is quantitative approach while the data analysis technique is a correlation. The results of the study showed that School Identity had an effect on School Reputation